Replication of the plasmid pBR322 under the control of a cloned replication origin from the single-stranded DNA phage M13. - Cleary, J M (1980)
The replication origins of viral and complementary strands of bacteriophage M13 DNA are contained within a 507-nucleotide intergenic region of the viral genome. Chimeric plasmids have been constructed by inserting restriction endonuclease fragments of the M13 intergenic region into the plasmid pBR322. Replication of these hybrid plasmids, under conditions not permissive for the plasmid replicon, depends on specific segments of the M13 origin region and on the presence of M13 helper virus. Thus M13-infected polA- Escherichia coli can be transformed to ampicillin resistance by hybrid plasmids that have a functional M13 origin. Cells transformed to drug resistance by plasmids bearing M13 origin sequences contain the duplex chimeric DNA at high copy number but do not accumulate significant amounts of single-stranded plasmid DNA. Rare transducing phages carrying single-stranded chimeric DNA are produced and can be detected by their ability to transduce cells to ampicillin resistance. Plasmids containing a 270-nucleotide fragment from the gene II-proximal half of the intergenic region produce transformants at high frequency under nonpermissive conditions. A central Hae III fragment, Hae III-G, containing the nucleotide sequence coding for the RNA primer for the complementary strand and the nicking site for gene II protein, is sufficient for plasmid replication in M13-infected polA- cells but not for high frequency transformation. Additional sequence information on the gene II side of the Hae III-G fragment is necessary for efficient transformation by the plasmid DNA.